Shear Wave Elastography May Be Superior to Greyscale Median for the Identification of Carotid Plaque Vulnerability: A Comparison with Histology - Garrard, J. W.; Ummur, P.; Nduwayo, S.; Kanber, B.; Hartshorne, T. C.; West, K. P.; Moore, D.; Robinson, T. G.; Ramnarine, K. V. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: There is a need to develop methods that reliably quantify characteristics associated with vulnerable carotid plaque. Greyscale median (GSM) and shear wave elastography (SWE) are two techniques that may improve individual plaque risk stratification. SWE, which quantifies Young’s Modulus (YM) to estimate tissue stiffness, has been researched in the liver, breast, thyroid and prostate, but its use in carotid plaques is novel.Materials and Methods: The aim of this study was to quantify YM and GSM of plaques and compare to histology. 25 patients (64 % male) with a mean age of 76 underwent both clinical and SWE imaging. The mean GSM was quantified over a cardiac cycle. The mean YM was quantified in multiple regions within the plaque over 5 frames. Histological features were assessed following carotid endarterectomy.Results: The mean YM of unstable plaques was significantly lower than that of stable plaques (50.0kPa vs. 79.1kPa; p = 0.027). The presence of intra-plaque hemorrhage, thrombus and increasing numbers of foam cells was also associated with a significantly lower YM. Plaque YM did not correlate well with plaque GSM (r = 0.12). The mean plaque GSM was the same in both unstable and stable plaques. Fibrous plaques had a significantly higher GSM (p = 0.036).Conclusion: In conclusion, SWE provides additional information on plaque stiffness which may be of clinical benefit to help identify vulnerable plaque, and warrants further study.
Keywords: carotid arteries; blood vessels; vascular; ultrasound; ischemia/infarction